The Influence of Ship Crew Job Involvement on Safety Performance in Enhancing Maritime Safety and Security Systems - Joko Purnomo; Irfan Fouzun; Muh. Firah Ramadhan Umar; Muhammad Rifani; Sappewali Sappewali (International Journal of Social Science and Humanity, 2024)
Job Involvement is a situation in which an individual feels a psychological attachment to their work and holds a strong belief in completing their tasks to achieve a high level of self-esteem. Safety performance refers to the worker's performance in prioritizing safety in the workplace by adhering to the applicable health and safety regulations. The purpose of this study is to determine the effect of Job Involvement on Safety Performance among ship crew members in improving the safety and security system of maritime operations. The research was conducted at PT. Tonasa Lines, Biring Kassi, Pangkep Regency, South Sulawesi Province. The sample in this study consisted of 100 participants. The sampling techniques used in this research were both probability sampling and non-probability sampling. The method used in this research was quantitative, using the Job Involvement and Safety Performance scales. The data analysis was performed using the Product Moment correlation technique with the assistance of the SPSS 28.0 for Windows program. The results showed a significant positive relationship between the Job Involvement variable and Safety Performance in improving the maritime safety and security system. The significance level was below or equal to 0.040 (p ˃ 0.01), so Ha is accepted and Ho is rejected with a 5% margin of error probability.